Exploring Language Assessment Literacy in EFL Classroom: A Case Study of EFL Teachers at a State Junior High School in Pekanbaru - Lilis Septiawati; Abdul Hadi (Journal of Educational Sciences, 2026)
This study aims to explore the Language Assessment Literacy of English as a foreign language (EFL) teachers in English language learning at SMP Negeri 9 Pekanbaru. This study uses a qualitative approach with a case study design. The research subjects consisted of three English teachers. Data were collected through semi-structured interviews, classroom observations, and Focus Group Discussions (FGD) with students. The results showed that EFL teachers' Language Assessment Literacy was integrated into their daily teaching practices. Assessment was carried out simultaneously with the teaching process through informal strategies such as oral questions, observations, direct feedback, and learning tasks. Teachers' assessment practices are formative, with the aim of monitoring student understanding, helping teachers make learning decisions, and supporting the student learning process. Although teachers rarely use the term assessment theoretically, their practices demonstrate an implicit understanding of assessment principles, such as appropriateness of objectives, fairness, and relevance to learning. In addition, this study found that teachers' LAL is influenced by internal and external factors. Internal factors include teaching experience and teachers' beliefs about the role of assessment in learning. External factors include limitations in language assessment training, administrative burdens, curriculum demands, and diversity in student characteristics.